Development of Variable Angle Stand Engine Motorcycle - ahmad osman, muhammad hafiz; Ibrahim, Badaruddin; Norlida Shaari (Research and Innovation in Technical and Vocational Education and Training, 2025)
The motor industry is a very large industry, it has also covered the whole of Asia and the world market. In addition, in Malaysia there are many shops that sell motor accessories. Not counting the young and old who are interested in this motorsport. There are groups that make it a hobby as well as a source of livelihood, especially in the field of motoring. However, when compared to a large-scale motor workshop, it has a variety of equipment compared to a small-scale motor workshop. The main focus of this project is to identify the daily problems in carrying out work activities, especially in maintaining motorcycle engines. The purpose of the researcher is to help the problems faced by small and medium industries (SME) by designing products that can withstand the weight of motorcycle engines for workers who do any maintenance on motorcycle engines. Based on experiments carried out around Perlis at the Workshop A workshop. This product has been tested with its functionality variable angle stand engine motorcycle has been proven to save time and practical in its use. This project has also received positive views from motorcycle workshop operators with almost 6 years of experience. The researcher also used the engineering design process (EDP) model to solve problems by analyzing problems before interpretation. As a result of design selection, three types of design are developed. From the first design to the final design is an improvement from the suggestions from the workshop itself. The third sketch becomes the choice. The researcher succeeded in developing this product but had to go through several testing processes where the product was done based on advice from experts. The experiment conducted is to test the durability of the product in terms of the ability to withstand the weight of a motorcycle engine. For the average weight of a motorcycle engine which is 19.7 kg for a horizontal engine and 25.5 kg for a vertical engine. In terms of time, it can also be concluded that it can save time in doing the maintenance process. With an average of 16.4 minutes for horizontal engines and also 23.2 minutes for vertical engines.